Pengaruh Pengalaman Pelanggan Dan Kepercayaan Terhadap Loyalitas Pelanggan Pada Jasa Pengiriman Barang Sicepat Ekspres Di Kecamatan Lasusua Kabupaten Kolaka Utara - Khatimah, Usnul; Stiadi, Muhamad; Zul Bay, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
This study was conducted to analyze the extent to which customer experience and trust influence customer loyalty toward SiCepat Ekspres delivery services in Lasusua District, North Kolaka Regency. A quantitative approach was used, employing the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). Data were collected from 130 respondents who had used SiCepat Ekspres services in Lasusua more than three times. The findings indicate that customer experience has a positive and significant effect on customer loyalty, and trust also has a positive and significant impact on customer loyalty.